Can be Synergized Carbon Tax and Carbon Trading in the Forestry Sector ? - Sofitri, Liliek (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
Deforestation and forest degradation largely contribute to global greenhouse gas (GHG) emissions. Innovative economic solutions tough their integration in the forestry sector is still under researched notably in tropical forest-rich countries. This study analysis how combining a carbon tax with ETS in the forestry sector might improve efforts at emission reduction, solve policy and implementation issues. Methods: a Systematic Literature Review (SLR) approach using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, combined with qualitative content analysis. A total of 45 academic articles and policy reports were analysed and categorized into three thematic areas: (1) policy design, comparing different carbon tax and ETS models; (2) economic and environmental impacts, and (3) global case studies, examining successful implementations in Brazil, Sweden, and California. Findings shows that by synergizing ETS and carbon tax it could strengthen forestry's sector on carbon mitigation strategies, by ensuring both price stability and market adaptability. While ETS generates economic incentives for carbon sequestration schemes based on forests, carbon tax systems set a price floor, therefore limiting too great volatility in carbon pricing. Three case studies show the advantages of a combined strategy: By using carbon tax income from the energy sector, Brazil's Amazon Fund funded projects aimed at preventing deforestation; this resulted in a 70% drop in deforestation between 2005 and 2012. Sweden implemented the highest carbon tax globally while maintaining economic stability through a hybrid voluntary carbon market, allowing industries greater compliance flexibility. California ensured in keeping carbon pricing by successfully combining a Cap-and- Trade system with transportation sector carbon levies, therefore encouraging investments in forest preservation initiatives. In conclusion, Indonesia has a great chance to lower carbon emissions and support sustainable forestry management by effectively combining an ETS with a carbon price and mitigate the challenges.